FUNDS ALLOCATION AND MANAGEMENT OF STAFF DEVELOPMENT PROGRAMMES IN UNIVERSITIES IN NORTH WEST ZONE, NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study examined funds allocation and management of staff development programmes in Universities in North West Zone, Nigeria. Two research questions and hypotheses guided the study. The study adopted the descriptive survey research design with a population of 25,020, while the sample size of the study was 444 stakeholders chosen through the simple random sampling technique. The instrument used for the collection of data was a self-structured questionnaire titled, “Funds Management Development Programmes Questionnaire” (FMDPQ) with a reliability coefficient index of ‘r’ = 0.97 obtained through the Cronbach alpha method. The questionnaire was structured on 5 points type rating scale responses of Strongly Agree (SA), Agree (A), Undecided (U) Disagree (D) and Strongly Disagree (SD). Data were analysed using frequency counts and percentages for the research questions while the hypotheses were tested using One-Way Analysis of Variance (ANOVA) at p